Fungus-growing ants (Hymenoptera: Formicidae) on Santa Catarina Island, BrazH: patterns of occurrence - Cortés Lopes, Benedito (Universidad de Costa Rica, 2000)
A taxonomic survey on fungus-growing ants (Attini) was made at 14 beaches on Santa Catarina Island (SC), Brazil. The samplings were manual, in soil or Iitterfall, in the following habitats: sandy beach, herbaceous vegetation and shrubby vegetation. From 12 species of Attini (ten of Acromynnex Mayr and two of Cyphomyrmex Mayr), the most frequent were Cyphomynnex morschi Emery and Acromynnex crassispinus Forel, collected, respectively, on eight and ten of the monitored beaches. Altogether, Sorensen's simílarity coefficients were hígh (range: 0.59-0.80), in spite of the lower numbers of ant species on sandy beaches.